Consultee-Centered Consultation: Contemporary Perspectives and a Framework for the Future. Issue 1 (2nd January 2017) - Newman, Daniel S.; Ingraham, Colette L.
ABSTRACT: Consultee-centered consultation (CCC) is a familiar, but historically understudied, model of consultation. This Special Issue of the Journal of Educational and Psychological Consultation summarizes, supplements, and updates the CCC research base; considers the role of CCC in contemporary school and community settings; and calls for and helps guide future CCC research and practice. This introduction to the Special Issue begins with a definition of CCC, individuates the model from its historical roots in mental health consultation, and provides a timeline of significant events in the evolution of the CCC model. Next, each article in the Special Issue is previewed in order to highlight unique contributions made to the CCC literature. Collectively, these articles provide a summary of the current state of CCC, multicultural frameworks for CCC training and practice, and multiple directions for future research.